International criminal justice: from the idea to modern system - A. G. Volevodz (Vestnik MGIMO-Universiteta)
Profound concern of international community about serious violations of basic principles and admitted rules leads to wide spread practice of establishing and functioning of international courts of criminal justice. The article touches upon the history of legal basis of international criminal justice, modern models of establishing and functioning of international criminal courts, and signs, that consolidate them into modern system of international criminal justice.